Housing development and urbanisation in China - Yao, Shujie; Luo, Dan; Wang, Jianling (Wiley, 2014)
Rapid urbanisation and rising income have led to a strong demand for housing in urban China. However, housing development has been distorted by speculation, income inequality and lack of government support for low-cost houses. In recent years, house prices become so high, making the vast majority of urban residents unable to afford, whereas rich families are able to buy many and leave them vacant. Income inequality is a major cause for rising house prices, which, in turn, exaggerates income inequality further. This vicious relationship has caused social tension between the rich and the poor and unhappiness among the middle- and low-income groups. This paper discusses the factors responsible for the housing bubble in China and recommends appropriate policies to resolve this problem.